How Capital Adequacy, Liquidity and Profitability Impact Financial Distress in Islamic Rural Banks in Indonesia - Rizky Fadhillah; Nahdatus Syaadah; Mairijani Mairijani; Mahyuni Mahyuni (International Journal of Economics, Commerce, and Management, 2024)
Competition in the banking industry is increasingly rapid at this time requiring each bank to have a stable healthy financial condition to avoid difficult financial conditions (financial distress). The purpose of this study was to determine how the influence of the Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), and Return on Equity (ROE) on the possibility of financial distress in Sharia Rural Banks registered with the Financial Services Authority in 2020-2023. The type of research used is descriptive quantitative research with the data source used is secondary data obtained from the financial statements of each Sharia Rural Bank. The results of this study found that the variables CAR, FDR, and ROE partially and simultaneously had a positive and significant effect on financial distress. The three independent variables together have an influence of 84.8% on the dependent variable, while the remaining 15.2% is influenced by other variables outside this study.